Unraveling the infection process of garlic by Fusarium proliferatum, the causal agent of root rot - CHRÉTIEN, Paul L.; LAURENT, Sandrine; BORNARD, Isabelle; TROULET, Claire; EL MAÂTAOUI, Mohamed; LEYRONAS, Christel (Phytopathologia Mediterranea, 2020)
Since the mid-2000s, and despite demanding production rules, Fusarium proliferatum (Matsushima) Niremberg has been found on garlic heads during storage inducing root and bulbs rots. Brown spots on the surface of garlic cloves and water-soaking of heads were noted. Histological observations of the fungus during early stages of infection were made from clove to the cellular levels. Fusarium proliferatum germinates, colonizes roots and degrades the outer root and parechchyma cell layers 72 h post inoculation. Conidium germination and host colonization are facilitated by the emergence of garlic roots, creating cellular debris and natural wounds. Hyphae of the pathogen did not penetrate healthy host cells and appeared to degrade them before penetration. These results provide understanding of when and how quickly F. prolife-ratum penetrates garlic bulbs. This is a primary step towards elucidating the life cycle of this pathogen during the garlic drying process, and development of an efficient and sustainable bulb rot management strategy.